Factors associated with initiation of antiretroviral therapy in the advanced stages of HIV infection in six Ethiopian HIV clinics, 2012 to 2013. Issue 1 (22nd April 2016) - Nash, Denis; Tymejczyk, Olga; Gadisa, Tsigereda; Kulkarni, Sarah Gorrell; Hoffman, Susie; Yigzaw, Muluneh; Elul, Batya; Remien, Robert H; Lahuerta, Maria; Daba, Shalo; El Sadr, Wafaa; Melaku, Zenebe
Abstract : Introduction: Most HIV‐positive persons in sub‐Saharan Africa initiate antiretroviral therapy (ART) with advanced infection (late ART initiation). Intervening on the drivers of late ART initiation is a critical step towards achieving the full potential of HIV treatment scale‐up. This study aimed to identify modifiable factors associated with late ART initiation in Ethiopia. Methods: From 2012 to 2013, Ethiopian adults ( n =1180) were interviewed within two weeks of ART initiation. Interview data were merged with HIV care histories to assess correlates of late ART initiation (CD4+ count <150 cells/µL or World Health Organization Stage IV). Results: The median CD4 count at enrolment in HIV care was 263 cells/µL (interquartile range (IQR): 140 to 390) and 212 cells/µL (IQR: 119 to 288) at ART initiation. Overall, 31.2% of participants initiated ART late, of whom 85.1% already had advanced HIV disease at enrolment. Factors associated with higher odds of late ART initiation included male sex (vs. non‐pregnant females; adjusted odds ratio (aOR): 2.02; 95% CI: 1.50 to 2.73), high levels of psychological distress (vs. low/none, aOR: 1.96; 95% CI: 1.34 to 2.87), perceived communication barriers with providers (aOR: 2.42, 95% CI: 1.24 to 4.75), diagnosis via provider initiated testing (vs. voluntary counselling and testing, aOR: 1.47, 95% CI: 1.07 to 2.04), tuberculosis (TB) treatment prior to ART initiation (aOR: 2.16, 95% CI: 1.43 to 3.25) and a gap in care of six months or more prior to ART initiation (aOR: 2.02, 95% CI: 1.10 to 3.72). Testing because of partner illness/death (aOR: 0.64, 95% CI: 0.42 to 0.95) was associated with lower odds of late ART initiation. Conclusions: Programmatic initiatives promoting earlier diagnosis, engagement in pre‐ART care, and integration of TB and HIV treatments may facilitate earlier ART initiation. Men and those experiencing psychological distress may also benefit from targeted support prior to ART initiation.